Changes of Plasma Coagulation and Fibrinolysis in Response to Mental Stress - Jern, Christina; Eriksson, Elsa; Tengborn, Lilian; Risberg, Bo; Wadenvik, Hans; Jern, Sverker (Thrombosis and Haemostasis, 1989)
To study the effects of standardized mental stress (arithmetic and the Stroop color word test) on plasma coagulation and fibrinolysis, blood samples were obtained before, during, and after 20 minutes of mental stress from 10 healthy, non-smoking young males aged 22 to 30 years. Reactions were compared with those observed during physical exercise and infusion of adrenaline. Both von Willebrand factor antigen and factor VIII coagulant activity increased significantly in response to mental stress (95 ± 28 vs 123 + 56%; p <0.05 and 125 ±54 vs 217 ± 170%; p <0.05, respectively). There was also a significant increase of factor VII coagulant activity (86 ± 31 vs 108 + 51%; p <0.05). Furthermore, mental stress caused an activation of the fibrinolytic system with an elevation of tissue plasminogen activator activity and tissue plasminogen activator antigen (0.80 ± 0.48 vs 1.23 ± 0.96 IU/ml; p = 0.076 and 4.38 ± 1.87 vs 5.78 ± 2.58 IU/ml; p <0.01). Fibrinogen concentration increased during stress (1.95 ± 0.29 vs 2.11 ± 0.27 g/1; p <0.05). Similar but more pronounced responses were observed during exercise and adrenaline infusion. Parallel to the increases in coagulation and fibrinolytic factors there were significant increases in heart rate, and systolic and diastolic blood pressure. It is concluded that mental stress has significant effects on plasma coagulation and fibrinolysis, and that it could thus affect important risk factors for cardiovascular disease.
Keywords: Mental stress; Psychosocial factors; Blood coagulation factors; Fibrinolysis